If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 19 = 2y + 10 Reorder the terms: 19 + 4y = 2y + 10 Reorder the terms: 19 + 4y = 10 + 2y Solving 19 + 4y = 10 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 19 + 4y + -2y = 10 + 2y + -2y Combine like terms: 4y + -2y = 2y 19 + 2y = 10 + 2y + -2y Combine like terms: 2y + -2y = 0 19 + 2y = 10 + 0 19 + 2y = 10 Add '-19' to each side of the equation. 19 + -19 + 2y = 10 + -19 Combine like terms: 19 + -19 = 0 0 + 2y = 10 + -19 2y = 10 + -19 Combine like terms: 10 + -19 = -9 2y = -9 Divide each side by '2'. y = -4.5 Simplifying y = -4.5
| 2x+3-5(x+1)=6x+5 | | 180=2x+(x+10)+(2x-30) | | [x]=10 | | 3-5(7y-11)= | | 0.14(y-9)+0.10=0.04y-0.01(60) | | x+189326=12 | | 6x^2=-24 | | -4(3x-1.5)+7=39 | | 50+(2x-4)=90 | | -1(x-9)+4x= | | 10-5x=55 | | 0.7(3.90-9x)=5.6x | | 3x-36+7=7 | | x^2-7x+49=0 | | 5+22a=2+10 | | 7x+(3x-5)+(8x+5)=180 | | 0=-16t^2+96t+160 | | -4(-3x+6)-2x= | | 1(x+42)-3=4(6x-4)+x | | x^3-x^2-6x+6=0 | | 3g=2g+15 | | .3x-4x+1.2x=.6 | | 7a+5a=132 | | x+20+0.06(x+20)=58 | | 6(y+4)=30 | | 10+x-17x=14 | | (2x+5)-5=-2 | | (-0.81)+(-7.2)-5.4= | | 0.05(7x+36)=0.4X+12 | | 4(c-1)=16 | | 0=13x^2+8x+236 | | Y=13x^2+8x+236 |